Game-Based Approach as an Intervention in Enhancing Students’ Fraction – Solving Skills - Torio, Jason; Venturillo, Jim Ryan (JPAIR Institutional Research, 2025)
Mastering fractions remains a significant challenge for students, with 96.53% (n=167) of Grade 7 students failing assessments covering addition, subtraction, multiplication, and division of fractions. To address this issue, this study investigated the effectiveness of Game-Based Learning (GBL) in improving students’ fraction-solving skills. Using a quasi-experimental design, the research involved 20 Grade 7 students from a public junior high school. Data were collected through validated pre-test and post-test instruments, aligned with the problem set and rigorously assessed for reliability. The results revealed significant improvements across all fraction operations, with notable progress in addition (t = -3.75, p = 0.000), subtraction (t = - 8.35, p = 0.000), and multiplication (t = -4.42, p = 0.000). Although division remained the most challenging area (t = -1.910, p = 0.000), students still demonstrated measurable gains, suggesting partial success in bridging learning gaps. The findings highlight GBL as an effective pedagogical strategy for enhancing fraction proficiency, fostering an engaging, and student- centered learning environment. The approach’s success is attributed to immediate feedback, contextualized practice, and increased motivation, making it a viable tool for improving mathematical competency. This study contributes to the growing body of evidence supporting GBL’s potential in mathematics education, particularly in addressing foundational challenges like fraction operations.